2020
DOI: 10.1002/jor.24678
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise facilitated rotator cuff healing is coupled with regulating periphery neuropeptides expression in a murine model

Abstract: Postoperative exercise has been found able to accelerate bone‐tendon (B‐T) healing. In this study, we systematically compared tendon‐to‐bone healing in mice subjected to postoperative treadmill exercise and free cage recovery in a murine rotator cuff repair model. Specifically, C57BL/6 mice underwent unilateral supraspinatus tendon (SST) detachment and repair were randomly allocated into treadmill group and control group. Treadmill group received daily treadmill running initiated from postoperative day 7 while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 49 publications
0
45
0
Order By: Relevance
“…48 Previous studies have established a method for evaluating subchondral bone at the BTI during the healing process by SR-mCT in the X-ray Imaging and Biomedical Application Beamline of the SSRF. 27,42,51 In this study, various postoperative treadmill rehabilitation programs demonstrated different qualities of subchondral bone at the BTI by SR-mCT. We observed that the morphological features of the healing interface at the SST enthesis and the subchondral bone quality continued improving with increasing intensity of the treadmill exercise.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…48 Previous studies have established a method for evaluating subchondral bone at the BTI during the healing process by SR-mCT in the X-ray Imaging and Biomedical Application Beamline of the SSRF. 27,42,51 In this study, various postoperative treadmill rehabilitation programs demonstrated different qualities of subchondral bone at the BTI by SR-mCT. We observed that the morphological features of the healing interface at the SST enthesis and the subchondral bone quality continued improving with increasing intensity of the treadmill exercise.…”
Section: Discussionmentioning
confidence: 65%
“…38 Rabbits are popular 6,42 because they are mild tempered and relatively easy to handle, but they are not able to tolerate the stress of surgery and infectious diseases as well as rodents can. 31 In particular, mouse models are useful for studying a wide range of RC pathologies 3,51 because their cellular and tissue physiology is close to that of humans; further, mouse models are more advantageous than rat models in terms of the availability of genetically altered strains to test the effects of specific signaling pathways and molecule changes on BTI development and repair. 3 Many strategies are used to evaluate the BTI healing process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations